Transport (and logistic) integration of Slovenia with EU - Trupac, Igor (Promet - Traffic&Transportation, 2012)
The article deals with transporl (and logistic) integration ofSlovenia with EU. Because of its position Slovenia has goodopportunities for transportation activities. Transpmtation (andlogistics) is also of extraordinwy imp01tance for economic developmentand appearance on the European and other markets.